Avenues in supercritical carbon dioxide extraction and fractionation of lipids. - Hossain, Md Sohrab; Mohamed, Siti Hajar; Khalid, Aina Mardhia; Balakrishnan, Venugopal; Sarker, Md. Zaidul Islam (Elsevier, 2020)
Supercritical carbon dioxide (scCO2) offers an alternative ecofriendly method for the conventional solvent extraction of lipids. CO2-based fluids are ideal supercritical fluids thanks to their distinct characteristics, such as nonflammability, nontoxicity, abundance, and recyclability, as well as their ability to solubilize lipophilic substances. Many studies have been conducted on the lipids extraction and fractionation from various lipid sources using scCO2 with or without a co-solvent. These studies revealed that scCO2 is a predominant technology for the lipids extraction and fractionation from various lipid sources. The present review was conducted to determine the influence of scCO2 process parameters on the extraction and fractionation of lipids from various plant and animal sources. Further, the influences of various operating parameters for the lipid extraction and fractionation subjected scCO2 extraction technology were also reviewed.